2001
DOI: 10.1089/107632701753213219
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Excitation Laser Scanning Microscopy of Human, Porcine, and Rabbit Nasal Septal Cartilage

Abstract: Two-photon excitation laser scanning microscopy (TPM) was used to image human, porcine, and rabbit nasal septal cartilage. TPM provides optical sections of thick tissue specimens in situ without the use of exogenous dyes or need for tissue fixation. The cartilage tissue was imaged using near-infrared light generated by a mode-locked titanium/sapphire laser that was raster-scanned and coupled to an inverted microscope. Absorption of two photons by endogenous molecules and subsequent fluorescence was filtered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Both natural and tissue-engineered cartilage have previously been studied using conventional histology and biochemical assays, as well as novel visualization techniques including magnetic resonance imaging (MRI) (Gray et al 2008), contrast-enhanced microcomputed tomography (lCT) (Palmer et al 2006), Fourier transform infrared imaging spectroscopy (FT-IRIS) (Bi et al 2007), and multiphoton microscopy (Wong et al 2001;Yeh et al 2005;Mansfield et al 2006;Lee et al 2006). Histology and biochemical assays have been traditionally used to either monitor the spatial distribution of ECM or to quantify the amount and type of matrix macromolecules in cartilage; however, those methods are rather timeconsuming and subject to distortion artifacts and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Both natural and tissue-engineered cartilage have previously been studied using conventional histology and biochemical assays, as well as novel visualization techniques including magnetic resonance imaging (MRI) (Gray et al 2008), contrast-enhanced microcomputed tomography (lCT) (Palmer et al 2006), Fourier transform infrared imaging spectroscopy (FT-IRIS) (Bi et al 2007), and multiphoton microscopy (Wong et al 2001;Yeh et al 2005;Mansfield et al 2006;Lee et al 2006). Histology and biochemical assays have been traditionally used to either monitor the spatial distribution of ECM or to quantify the amount and type of matrix macromolecules in cartilage; however, those methods are rather timeconsuming and subject to distortion artifacts and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…The density of collagen fibers was studied in the extracellular matrix of the fibroblast tissue model using multiphoton microscopy (MPM) as previously described (1,57). Briefly, collagen-embedded NHLF matrices were lifted onto microscope slides and covered with full-length coverslips, thinness 1 (Fisher Scientific, Pittsburgh, PA), and excited with a 100-fs Titanium: Sapphire laser as the multiphoton excitation source.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Pyridinoline is one such compound, as well as aromatic groups in the proteins and nucleic acids, such as NADH (reduced form of nicotinamide adenine dinucleotide) NADPH (reduced form of nicotinamide adenine dinucleotide phosphate), and flavoproteins (Wong et al, 2001). A complete understanding of the exact sources and nature of fluorophores in cartilage is not fully established (Tadrous et al, 2003), making it difficult to quantify fluorescence using suggested standards, such as the molecules of equivalent soluble fluorochrome (MESF; Schwartz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%